A Phase 2, Double-Blind, Placebo-Controlled, Randomized Study of Fresolimumab in Patients With Steroid-Resistant Primary Focal Segmental Glomerulosclerosis - Flavio Vincenti; Fernando C. Fervenza; Kirk N. Campbell; Montserrat Diaz; Loreto Gesualdo; Peter Nelson; Manuel Praga; Jai Radhakrishnan; Lorenz Sellin; Ajay Singh; Denyse Thornley-Brown; Francisco Veríssimo Veronese; et al. (Kidney International Reports, 2017)
Steroid-resistant focal segmental glomerulosclerosis (SR-FSGS) is a common glomerulopathy associated with nephrotic range proteinuria. Treatment goals are reduction in proteinuria, which can delay end-stage renal disease. Methods: Patients with SR-FSGS were enrolled in a randomized, double-blind placebo-controlled trial of fresolimumab, a monoclonal anti−transforming growth factor−β antibody, at 1 mg/kg or 4 mg/kg for 112 days, followed double-blind for 252 days (NCT01665391). The primary efficacy endpoint was the percentage of patients achieving partial (50% reduction) or complete (< 300 mg/g Cr) remission of proteinuria. Results: Of 36 enrolled patients, 10, 14, and 12 patients received placebo, fresolimumab 1 mg/kg, and fresolimumab 4 mg/kg, respectively. The baseline estimated glomerular filtration rate (eGFR) and urinary protein/creatinine ratio were 63 ml/min/1.73 m2 and 6190 mg/g, respectively. The study was closed before reaching its target of 88 randomized patients. None of the prespecified efficacy endpoints for proteinuria reduction were achieved; however, at day 112, the mean percent change in urinary protein/creatinine ratio (a secondary efficacy endpoint) was –18.5% (P = 0.008), +10.5% (P = 0.52), and +9.0% (P = 0.91) in patients treated with fresolimumab 1 mg/kg, fresolimumab 4 mg/kg, and placebo, respectively. There was a nonsignificant trend toward greater estimated glomerular filtration rate decline in the placebo group compared to either of the fresolimumab-treated arms up to day 252. Discussion: The study was underpowered and did not meet the primary or secondary endpoints. However, fresolimumab was well tolerated and is appropriate for continued evaluation in larger studies with adequate power.